2018
DOI: 10.1016/j.pmrj.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shockwave Treatment for Management of Upper and Lower Extremity Musculoskeletal Conditions: A Narrative Review

Abstract: Extracorporeal shockwave therapy (ESWT) is a technology that was first introduced into clinical practice in 1982 for urologic conditions. Subsequent clinical applications in musculoskeletal conditions have been described in treatment of plantar fasciopathy, both upper and lower extremity tendinopathies, greater trochanteric pain syndrome, medial tibial stress syndrome, management of nonunion fractures, and joint disease including avascular necrosis. The aim of this review is to summarize the current understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 83 publications
0
81
0
3
Order By: Relevance
“…Little evidence of long-term benefit from ESWT for lateral epicondylitis has been shown by Staples et al [30]. Recently, in a narrative review, Reilly et al [31] did not recommend a nerve block or an anesthetic in adduction to ESWT; they concluded that the NSAID's use can disrupt normal inflammatory pathways that may be responsible for treatment response. Moreover, the authors verified good functional outcomes of ESWTs in LE patients, supporting the theory that previous poor results study studies have created a variety of placebo ESWT conditions, not achieving complete blinding and comparative effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Little evidence of long-term benefit from ESWT for lateral epicondylitis has been shown by Staples et al [30]. Recently, in a narrative review, Reilly et al [31] did not recommend a nerve block or an anesthetic in adduction to ESWT; they concluded that the NSAID's use can disrupt normal inflammatory pathways that may be responsible for treatment response. Moreover, the authors verified good functional outcomes of ESWTs in LE patients, supporting the theory that previous poor results study studies have created a variety of placebo ESWT conditions, not achieving complete blinding and comparative effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular hypothesis advances the active role of the inflammatory response and leukocyte chemotaxis to generate the phagocytosis of the calcium deposit [16]. Moreover, ESWT may reduce pain through hyperstimulation of nociceptors/gate-control theory of pain transmission, altered pain receptor neurotransmission, and by increasing local pain inhibiting substances [20]. Stimulation of nociceptive C-fibers may not only play a role in analgesia, but also in tendon remodeling, as it may increase the release of neuropeptides, causing fibroblast stimulation and vasodilation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Radial shockwave therapy (R‐SWT) is a lower energy form of shockwave and has been described in allowing elite athletes safe return to competition . As compared to focused shockwave therapy, in which the greatest force generated occurs at a certain depth within the structure being treated, in R‐SWT the maximum force occurs at the skin surface, with subsequent dispersion of force with increased depth . We present two cases of chronic tendinopathy successfully treated in endurance runners using R‐SWT.…”
mentioning
confidence: 99%
“…Few options exist that offer athletes a safe method for expedited return to competition in refractory tendon disease. Standardized protocols for R‐SWT do not exist; however, studies with treatment sessions separated by 1 week, with a total of 3‐5 treatments, appear to be most effective …”
mentioning
confidence: 99%
See 1 more Smart Citation